Mechanical activation influence on the morphological properties of La2O3-TiO2-B. Issue 1 (April 2016) - Dolmatov, O; Zakusilov, V; Kuznetsov, M; Pimenov, N; Chursin, S
Abstract: The influence of mechanical activation of the powder mixture used to obtain the high-perfomance cathode for accelerating engineering with the SHS-method has been explored. The mechanically processed mixtures have been morphologically analyzed. The optimal modes of mechanical activation have been determined for the mixture.